Adult Onset Still's Disease (Faridpur Medical College Journal, 2017)
Adult Still's disease is rare disease presented with high spiking fever, joint pain, rash, organomegaly and serositis. It is difficult to diagnose as it closely mimics with many systemic diseases, so it can be diagnosed after exclusion of them. There are lots of diagnostic criteria, of them Yamaguchi's criteria is well established. Treatment consists of NSAIDS, corticosteroids & other immunosuppressive drugs. Course of the disease is unpredictable with relapse & remission in many cases. Here we present a 25 years old lady with Adult Onset Still's Disease.Faridpur Med. Coll. J. Jul 2016;11(2): 86-89